Amplatzer vascular plug IV for occlusion of pulmonary arteriovenous malformations in a patient with cryptogenic stroke - Surendranath R Veeram Reddy; Vishal G Patel; Sarah K Gualano (Wolters Kluwer Medknow Publications, 2014)
Paradoxical embolism resulting in cryptogenic stroke has received much attention recently, with the primary focus on patent foramen ovale (PFO). However, it is essential to be vigilant in the search for other causes of paradoxical embolic events, such as pulmonary arteriovenous malformations (PAVM). We describe successful closure of pulmonary AVM with a St Jude Medical (Plymouth, MN) Amplatzer TM vascular plug IV. The newer AVP-IV devices can be used for successful embolization of tortuous pulmonary AVM in remote locations where use of other traditional devices may be technically challenging.